2012
DOI: 10.1016/j.juro.2012.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insight into the Dynamics of Male Pelvic Floor Contractions Through Transperineal Ultrasound Imaging

Abstract: Purpose Transperineal ultrasound imaging (US) enables minimally invasive assessment of pelvic floor muscle function. Although commonly used in females, the approach has not been reported in males. This approach has advantages because the mid-sagittal view visualises a bony landmark and the entire urethral length. This allows investigation of displacement of multiple points along the urethra and the unique mechanical actions of multiple muscles that could influence continence. We used a new transperineal US tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 31 publications
2
61
0
Order By: Relevance
“…Furthermore, this protocol may be useful in differentiating between therapy responders and non-responders to inform intervention planning and enhance targeting of interventions to those patients whom would most benefit. Combining this transperineal approach with other sonographic investigations of the pelvic floor, such as those evaluating structure orientation and dynamic movements (Davis et al 2011; Stafford et al 2012; Stafford et al 2013), may lead to a robust evaluation protocol for individuals with CPPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this protocol may be useful in differentiating between therapy responders and non-responders to inform intervention planning and enhance targeting of interventions to those patients whom would most benefit. Combining this transperineal approach with other sonographic investigations of the pelvic floor, such as those evaluating structure orientation and dynamic movements (Davis et al 2011; Stafford et al 2012; Stafford et al 2013), may lead to a robust evaluation protocol for individuals with CPPS.…”
Section: Discussionmentioning
confidence: 99%
“…The first report using this approach meant to evaluate the orientation of anal-pelvic structures, i.e., anorectal angle and levator plate angle (Davis et al 2011). A similar transperineal approach has been reported in evaluation of the displacement and dynamic changes of pelvic structures during contraction of pelvic floor and anorectral muscles (Stafford et al 2012; Stafford et al 2013). These studies utilized a low-frequency curvilinear probe with data collection in a sagittal plane to evaluate the entire pelvic region.…”
Section: Introductionmentioning
confidence: 97%
“…Stafford et al measured the contraction of the pelvic floor muscles, clearly defining the displacement of the urethrovesical junction, ano--rectal junction and distal urethra in healthy young men (10,12). Davis et al measured men with chronic pelvic pain syndrome and concluded that men with pain had a smaller ano-rectal angle compared to men without pain (11).…”
Section: Discussionmentioning
confidence: 99%
“…Stafford et al (page 1224) from Australia and the U.S. investigated the role of 2-dimensional midsagittal perineal ultrasound in 10 continent men noting contractions along specific points of the urethra. 7 They were able to discern contractions by levator ani, striated urethral sphincter and bulbocavernosus muscle groups. Furthermore, displacement was measured for the urethral sphincter and urethrovesical junction.…”
Section: Dynamics Of Male Pelvic Floor Contractions Through Perinealmentioning
confidence: 99%